Kebijakan Kepala Sekolah dan Madrasah Dalam Menerapkan P-5/PPRA - Maulina, Lailatul (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the policies of school and madrasah principals in implementing P5/PPRA at SMAN 2 Pamekasan and MAN 2 Pamekasan, including the challenges and advantages encountered in the process. The research employed a qualitative approach with a collective instrumental case study design. Data were collected through observation, interviews, and documentation. The findings indicate that the formulation of policies by principals in implementing P5/PPRA is a strategic response to the Merdeka Curriculum framework. The policy process involves the issuance of formal decrees, followed by systematic planning and implementation stages. The primary challenges faced by both institutions relate to student engagement, while financial constraints were specifically identified at MAN 2 Pamekasan. The advantages of the policy implementation include character development, as well as the enhancement of students’ knowledge and skills. This study contributes to the discourse on educational leadership and may serve as a reference for policy implementation of P5/PPRA in senior high schools and Islamic senior high schools.